Phylogenetic insights into the genus Amblyomma in America, including the endangered species Amblyomma albopictum, Amblyomma macfarlandi, and Amblyomma usingeri. Issue 5 (4th July 2021) - Santodomingo, Adriana; Uribe, Juan E.; Lopez, Gustavo; Castro, Lyda R.
ABSTRACT: The genus Amblyomma Koch, 1844, is distributed in the Americas, Africa, Asia, and Oceania and is currently represented by 139 valid species, half of which are endemic to the Americas. This group of ticks has considerable ecological, economic, and public health importance. However, although many sequences and other information are available, investigations have been performed in isolated clades, and the evolutionary relationships of the genus Amblyomma are not evident. This study presents the phylogenetic relationships of the genus Amblyomma in America using probabilistic methods (Maximum Likelihood and Bayesian Inference). Partial sequences of five genes (four mitochondrial genes and one nuclear gene) from 69 species of Amblyomma were concatenated. Within the genus, some species have been described as endangered, mainly due to the status of their main host. In this study, sequences for the endangered species A. albopictum Neumann, 1899; A. macfarlandi Keirans, Hoogstraal and Clifford, 1973; and A. usingeri Keirans, Hoogstraal and Clifford, 1973, were determined for the first time. Although many phylogenetic relationships had strong statistical support, molecular data from different species must be increased to achieve better phylogenetic estimates in future studies.